Sidewalking : Coming to Terms with Los Angeles. - Ulin, David L. (Berkeley : University of California Press, 2015)
In Sidewalking, David L. Ulin offers a compelling inquiry into the evolving landscape of Los Angeles. Part personal narrative, part investigation of the city as both idea and environment, Sidewalking is many things: a discussion of Los Angeles as urban space, a history of the city's built environment, a meditation on the author's relationship to the city, and a rumination on the art of urban walking. Exploring Los Angeles through the soles of his feet, Ulin gets at the experience of its street life, drawing from urban theory, pop culture, and literature. For readers interested in the culture of Los Angeles, this book offers a pointed look beneath the surface in order to see, and engage with, the city on its own terms.
Cover -- Contents -- Acknowledgments -- Street, Haunting -- Los Angeles Plays Itself -- Falling Down -- Sidewalking -- Mapping History -- Miracle Mile -- A Walker, in the City.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Streets - California - Los Angeles; Electronic books